2011
DOI: 10.1007/s00268-011-1253-x
|View full text |Cite
|
Sign up to set email alerts
|

A Preoperative Predictive Scoring System for Postoperative Pancreatic Fistula after Pancreaticoduodenectomy

Abstract: The present scoring system satisfactorily predicted the occurrence of POPF and thus will be useful for the perioperative risk management of patients undergoing PD in a high-volume center hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 41 publications
7
108
2
4
Order By: Relevance
“…One studies described the development of a predictive model for POPF, based on perioperative risk factors [10]. Three studies derived a predictive model for POPF based on preoperative risk factors [8,13,17]. Intraoperative risk factors were used by one study to derive a predictive model of POPF [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One studies described the development of a predictive model for POPF, based on perioperative risk factors [10]. Three studies derived a predictive model for POPF based on preoperative risk factors [8,13,17]. Intraoperative risk factors were used by one study to derive a predictive model of POPF [12].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of geography, three articles were from Asia [8,17,18] and four articles were from Europe [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally reported that the incidence of clinically relevant post‐operative pancreatic fistulas after PD is 7.6–36.4%,1, 2, 3, 4, 5 in accordance to the definition of the International Study Group of Pancreatic Fistula (ISGPF) 6. Researchers have suggested factors that affect pancreatic leakage after PD, including male gender, advanced age, post‐operative albumin level, intraoperative bleeding, soft pancreatic parenchyma, small pancreatic duct, drain amylase level on post‐operative day one, pancreatic parenchymal thickness and surgeon volume, among others 1, 7, 8, 9, 10, 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%